Polysorbate 80 and Helicobacter pylori: a microbiological and ultrastructural study - Figura, Natale (BioMed Central, 2012)
BACKGROUND: The frequent occurrence of chemoresistant strains reduces the chances of eradication of H. pylori infection and prompted the investigation of non-antibiotic substances active against this organism. Some surfactants enhance the effectiveness of antibiotics for their permeabilizing properties towards bacteria. We examined the antimicrobial activity to H. pylori of the surfactant polysorbate 80, used alone and in association with amoxicillin, clarithromycin, metronidazole, levofloxacin and tetracycline. We also aimed to study the ultrastructural alterations caused upon H. pylori by polysorbate 80, alone and in combination with antibiotics. Twenty-two H. pylori strains were tested using the broth dilution method. After incubation, broth from each dilution was subcultured onto agar enriched with foetal bovine serum to determine the minimum bactericidal concentration (MBC). Synergistic effect of polysorbate 80 with antibiotics was investigated by the broth dilution and disc diffusion techniques. Ultrastructural alterations of organisms treated with polysorbate 80, alone and in association with antibiotics were analyzed by transmission electron microscopy. RESULTS: MBCs of polysorbate 80 ranged from 2.6 (1.1) μg/ml to 32 (0) μg/ml. Polysorbate 80 exerted a synergistic effect when associated with metronidazole and clarithromycin: polysorbate 80 and metronidazole MBCs decreased by ≥ 4 fold; clarithromycin MBCs for two resistant strains decreased by 20 and 1000 times. The principal alteration caused by polysorbate 80 consisted in the detachment of the outer membrane of bacteria. CONCLUSIONS: The bactericidal activity of polysorbate 80 and the synergistic effect of the association with metronidazole and clarithromycin could be useful in the treatment of H. pylori infection.